Involvement of the septation initiation network in events during cytokinesis in fission yeast - Dey, Sumit K. (J Cell Sci, 2018)
The septation initiation network (SIN), comprising a GTPase and a cascade of three protein kinases, regulates cell division in fission yeast Schizosaccharomyces pombe, but questions remain about its influence on cytokinesis. Here, we made quantitative measurements of the numbers of Cdc7p kinase molecules (a marker for SIN activity) on spindle pole bodies (SPBs), and on the timing of assembly, maturation and constriction of contractile rings via six different proteins tagged with fluorescent proteins. When SIN activity is low in spg1-106 mutant cells at 32°C, cytokinetic nodes formed contractile rings ∼3 min slower than wild-type cells. During the maturation period, these rings maintained normal levels of the myosin-II mEGFP–Myo2p but accumulated less of the F-BAR protein Cdc15p–GFP than in wild-type cells. The Cdc15p–GFP fluorescence then disintegrated into spots as mEGFP–Myo2p dissociated slowly. Some rings started to constrict at the normal time, but most failed to complete constriction. When high SIN activity persists far longer than normal on both SPBs in cdc16-116 mutant cells at 32°C, contractile rings assembled and constricted normally, but disassembled slowly, delaying cell separation.